Transient improvement of urticaria induces poor adherence as assessed by Morisky Medication Adherence Scale‐8. Issue 11 (5th June 2015) - Kaneko, Sakae; Masuda, Koji; Hiragun, Takaaki; Inomata, Naoko; Furue, Masutaka; Onozuka, Daisuke; Takeuchi, Satoshi; Murota, Hiroyuki; Sugaya, Makoto; Saeki, Hidehisa; Shintani, Yoichi; Tsunemi, Yuichiro; et al.
Abstract Poor adherence to medication is a major public health challenge. Here, we aimed to determine the adherence to oral and topical medications and to analyze underlying associated factors using the translated Japanese version of Morisky Medication Adherence Scale‐8 regarding urticaria treatment. Web‐based questionnaires were performed for 3096 registered dermatological patients, along with a subanalysis of 751 registered urticaria patients in this study. The adherence to oral medication was significantly associated with the frequency of hospital visits. Variables that affected the adherence to topical medication included age and experience of drug effectiveness. The rate of responses that "It felt like the symptoms had improved" varied significantly among the dermatological diseases treated with oral medications. Dermatologists should be aware that adherence to the treatment of urticaria is quite low. Regular visits and active education for patients with urticaria are mandatory in order to achieve a good therapeutic outcome by increasing the adherence.